Blended Dry and Hot Events Index for Monitoring Dry‐Hot Events Over Global Land Areas. Issue 24 (18th December 2021) - Wu, Haijiang; Su, Xiaoling; Singh, Vijay P.
Abstract: The amplifying effects of disasters caused by compound dry and hot extremes (dry‐hot events) have attracted widespread attention. This study presents a novel Blended Dry and Hot Events Index (BDHI) considering various dry and hot conditions (i.e., dry/hot, dry/cool, wet/hot, and wet/cool conditions). BDHI was applied to monitor dry‐hot events over global land areas during the 1950–2019 period and its performance was compared against that of the Standardized Compound Event Indicator (SCEI), which includes certain unsatisfactory or unclear features. We found that BDHI comprehensively reflected the characteristics of meteorological drought and temperature anomalies in monitoring dry‐hot events. Many regions around the globe have been experiencing more severe dry‐hot events since the 1990s, especially Russia, the USA, China, India, Australia, southern Africa, Europe, and South America. The proposed index is expected to serve as a potential tool for monitoring dry‐hot events and will be useful for managing and mitigating associated risks. Plain Language Summary: Concurrent meteorological drought and hot extremes (dry‐hot events) can have devastating impacts on agricultural production, water security, and ecological health. Recent decades, particularly in the twenty‐first century, have witnessed numerous adverse dry‐hot events under anthropogenic climate change. However, existing indexes for monitoring dry‐hot events do not consider or adequately reflect the numerous dry and hot conditions, which may lead to misleading or inconclusive results. To overcome this limitation, we present a novel Blended Dry and Hot Events Index (BDHI) that can depict dry‐hot events considering various dry and hot conditions (i.e., dry/hot, dry/cool, wet/hot, and wet/cool conditions). Results show that the severity and spatial extent of dry‐hot events have significantly increased after the 1990s over global land areas, especially in Russia, the USA, China, India, Australia, southern Africa, Europe, and South America. Additionally, the percentage of areal coverage of global dry‐hot events during June‐July‐August (December‐January‐February) in the 1998–2019 (1995–2019) period was larger than in the 1950–1997 (1950–1994) period, based on the ERA5 reanalysis data set. The exacerbation of dry‐hot events threatens water availability, crop production, and ecosystem services. Key Points: A Blended Dry and Hot Events Index is proposed to monitor dry‐hot events over global land areas The severity and area coverage percentage of dry‐hot events around the globe rapidly increased after the 1990s The relative contributions of changes in SPI and STI to dry‐hot events vary with regions and seasons